JILBAB SEBAGAI SIMBOL KOMUNIKASI DI KALANGAN MAHASISWA UNIVERSITAS HASANUDDIN (Studi Komunikasi Nonverbal) - Besse Risnayanti; Hafied Cangara (KAREBA : Jurnal Ilmu Komunikasi, 2011)
AbstractThis research is a study of nonverbal communication behaviors of students covered by a descriptive qualitative. Inthis study obtained of 145 studens which wearing veil as a sample, withc cluster sampling technique in which aquota sample drawn by the percentage of 2% of each faculty. To obtain data conducted by distributingquiestionaries, in depth interviewes, direct observation and literature study, then analyzed qualitatively. Discussionof this research uses the concept of nonverbal communication and the concept of symbolic interactionism byBlumer. Result showed that student’s view on the hijab covering ideology, adaptation and identity. From the contextof Islamic ideology, “Clothes are mandatory for Muslims who have entered legally Baligh, because the commandsare written clearly covered in the Qur’an, where Muslim women are prohibited from revealing private parts exceptthe face and hands.” From the context of identity, “just as life-style headscarf.” More students to consider problemsand models wearing the headscarf that matched rather than syar’i according to Islam, and the trend is more the issuethan the issue of religious obligation. From the context of adaptation, ‘significant other’ very influental on thebehavior of students wearing the hijab as parents and family, and veiled student behavior based on a communityreference group. Students inclined have as a friend that similarity through ideology, vision in veil, hobby or style:“cognitive consistency”. AbstrakPenelitian ini dimaksudkan untuk mengetahui faktor-faktor yang memengaruhi mahasiswa Universitas Hasanuddinmemakai jilbab dari aspek komunikasi non-verbal. Penelitian dilakukan dengan metodi deskriptif kualitatif denganmelibatkan 145 orang mahasiswi pemakai jilbab sebagai sampel, yang dilakukan dengan cara cluster samplingdengan quota 2 persen pemakaian jilbab tiap fakultas. Data diperoleh melalui angket yang diedarkan, wawancaramendalam, pengamatan langsung, dan studi pustaka, kemudian dianalisis secara kualitatif. Pembahasan yangdilakukan dalam penelitian ini memakai konsep komunikasi non-verbal (isyarat) dan konsep interaksi simbolik dariBlumer. Hasilnya menunjukkan bahwa para mahasiswa yang memakai jilbab memiliki makna ideologi, penyesuaiandan jati diri. Dari konteks ideologi, Islam melalui Al-Qur’an mewajibkan kepada muslim perempuan yang sudahbaligh dilarang memperlihatkan bagian tubuh yang bersifat pribadi kecuali muka dan tangan. Dari konteks adaptasi(penyesuaian) para mahasiswi yang berjilbab banyak dipengaruhi oleh lingkungan, kelompok, dan komunitas sepertiorang tua dan keluarga. Sedangkan dari aspek jati diri, nampaknya selain sebagai simbol muslim juga sebagaiperilaku yang lebih sopan dalam berpakaian.